(untitled) (Shahid Kirti Multidisciplinary Journal, 2026)
Management Accounting Practices (MAP) play a crucial part in processes, methods, and tools which are used in companies or organization for decision making, satisfaction, and performance. Environment issues are tough tasks both at a local and global level. This study investigates the association between management accounting practices and the overall performance given by the commercial banks operating in Nepal. As well as, it aims to check the moderating role of management accounting practice regarding green strategy; it investigates the impact of green strategy management accounting practice on the organizational performance given by commercial banks. This study incorporates a focus on performance measurement, which incorporates satisfaction, as well as an investigation into the influence of green strategy functioning practices. Green strategy forthcoming in banks matches the current worldwide notion, which stresses their relevance. This study utilizes a descriptive survey method along with the use of quantitative strategies, conducting a survey through the distribution of 500 & 400 questionnaires among the managers & clients of six commercial banks in Nepal. 325 questionnaires have been returned from branch managers & 385 questionnaires returned from clients, which comprised 320 responses. The key findings are that MAPs are positively and significantly related to organizational performance and that MAPs are also positively and significantly related to green strategies. In addition, it was found that green strategies enhance the influence of MAPs on performance outcomes. Accordingly, good MAPs make a significant contribution to bank financial outcomes and customer satisfaction. It is recommended in this study that the Nepalese banking industries implement robust MAPs that are integrated with green strategies for comprehensively enhancing the overall organizational performance towards jointly maximizing economic and environmental benefits